Triple blending with superfine natural zeolite and condensed silica fume to improve performance of cement paste - Ng, P.L.; Chen, J.J.; Kwan, A.K.H. (International Conference “Environmental Engineering”, 2017)
Superfine natural zeolite (SNZ) is obtained by grinding natural zeolite to microfine-size, whereas condensed silica fume (CSF) is byproduct of ferrosilicon industry. Both SNZ and CSF are environmentally-friendly supplementary cementitious materials for mortar and concrete production. Owing to the high fineness and favourable grading of SNZ and CSF (the median particle sizes were 4 m and 0.4 m, respectively), the addition of SNZ and CSF could successively fill the voids between ordinary Portland cement (OPC) grains and increase the packing density of the binder, so as to reduce the volume of voids to be filled with water. Therefore, triple blending of OPC+SNZ+CSF can benefit the overall performance of cement paste by releasing more water for flowability improvement at the same water/binder (W/B) ratio, or adopting a lower W/B ratio for strength improvement at the same flowability requirement. This study evaluated the effects of adding SNZ and CSF on the packing density and water film thickness of binder. The experimental results proved that triple blending with SNZ and CSF could increase the packing density and improve the flowability and cohesiveness of cementitious paste.